Neonatal intensive care outcomes and resource utilisation of infants born <26 weeks in the former Trent region: 2001–2003 compared with 1991–1993. Issue 5 (1st December 2010) - Rattihalli, R R; Lamming, C R; Dorling, J; Manktelow, B N; Bohin, S; Field, D J; Draper, E S
Abstract : Objectives: To provide survival data and rates of severe disability at 2 years of corrected age in infants born prior to 26 weeks' gestation in 2001–2003 and to compare these outcomes with an earlier cohort from 1991 to 1993. Design: Population-based prospective cohort study. Setting: Former Trent region of UK covering a population of approximately five million and around 55 000 births per annum. Participants: The authors identified a 3-year cohort of infants born before 26 weeks' gestation between 1 January 2001 and 31 December 2003 from The Neonatal Survey (TNS). Questionnaires based on the Oxford minimum dataset were completed. Main outcome measures: Survival, service use and disability levels were compared between the 2001– 2003 cohort and the cohort from 1991 to 1993. Results: In 2001–2003, 0%, 18% and 35% of live born babies were alive at 2 years without any evidence of severe disability at 23, 24 and 25 weeks' gestation, respectively. Overall, of those children admitted to neonatal care, the proportion with no evidence of severe disability at 2 years corrected age improved from 14.5% in 1991–1993 to 26.5% in 2001–2003. There was an increase in the proportion of children with at least one severe disability, out of total admissions to neonatal unit (8% vs 17%) and of those assessed at 2 years (35% vs 39%). Conclusions: This study has shown an improvement in survival to discharge in babies admitted for neonatal care. However, this improved survival has been associated with an increase in the proportion of children with at least one severe disability at a corrected age of 2 years.